Effect of High-Humidity Hot Air Impingement Steaming on Cistanche deserticola Slices: Drying Characteristics, Weight Loss, Microstructure, Color, and Active Components - Ziping Ai; Yawen Lin; Yongkang Xie; Samir Mowafy; Samir Mowafy; Yue Zhang; Mengjia Li; Yanhong Liu (Frontiers in Nutrition, 2022)
Cistanche deserticola is one of the most precious herbal medicines and is widely used in the pharmaceutical and healthy food industries. Steaming is an important step prior to drying in the processing of C. deserticola. This research investigated the effects of high-humidity hot air impingement steaming (HHAIS) parameters such as temperature, time, and relative humidity (RH) on drying characteristics, weight loss, color, microstructure, and active components of C. deserticola slices. The results showed that the steaming process caused a weight loss in C. deserticola; however, increasing the RH reduced the weight loss. Starch gelatinization observed from the microstructure of the steamed samples explained their long drying time. The Page model can well fit the drying process with a high R2 (>0.956) under the drying conditions of 60°C and 6 m/s. Steaming increased the content of phenylethanoid glycosides, and the highest content was obtained at 95°C and 60% RH for 20 min, 75°C and 70% RH for 20 min, and 75°C and 60% RH for 30 min. The steamed samples appeared in an oil black color. When the color difference (ΔE) values were in the range of 16.79–20.12, the contents of echinacoside and acteoside reached the maximum. Steaming at 95°C and 60% RH for 20 min, 75°C and 70% RH for 20 min, and 75°C and 60% RH for 30 min are the optimum process conditions. The results from this work provide innovative steaming technology and suitable processing parameters for producing C. deserticola decoction pieces with a high quality, which will broaden its potential application in the functional health food industry.